1989
DOI: 10.1063/1.101287
|View full text |Cite
|
Sign up to set email alerts
|

Role of vanadium in organometallic vapor phase epitaxy grown GaAs

Abstract: The electrical and photoluminescent properties of vanadium incorporated into GaAs epitaxial layers from a VO(OC2H5)3 source during organometallic vapor phase epitaxy were examined. The vanadium concentration in the GaAs was controllably varied from 1016 to 1018 atoms cm−3. Deep level transient spectroscopy showed the presence of an electron trap at Ec−0.15 eV which increased in concentration with vanadium content of the epitaxial layers. A maximum value of 8×1015 cm−3 for this trap was obtained. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…The DLTS spectrum of sample B shows a wellpronounced peak around 90 K, labelled E1. We detected this E1 trap for different V concentrations, its amplitude increasing with the V concentration and reaching a maximum value of about 10 16 cm −3 for a V concentration of 2 × 10 18 cm −3 , in agreement with a previous report [11]. This observation indicates that the E1 defect is most likely associated with V doping.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The DLTS spectrum of sample B shows a wellpronounced peak around 90 K, labelled E1. We detected this E1 trap for different V concentrations, its amplitude increasing with the V concentration and reaching a maximum value of about 10 16 cm −3 for a V concentration of 2 × 10 18 cm −3 , in agreement with a previous report [11]. This observation indicates that the E1 defect is most likely associated with V doping.…”
Section: Resultssupporting
confidence: 92%
“…According to Akayama et al [10], and Terao et al [7], an oxygen-containing organometallic V precursor is needed to obtain SI material by VPE or OMVPE. However, Hobson et al found results in contradiction with this last conclusion [11]. Although they have used the same oxygen-containing precursor as that used by Akayama et al, VO(OC 2 H 5 ) 3 , they did not obtain a SI material by OMVPE.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, vanadium plays a mainly chemical role (gettering of donors) during the crystal growth process [30]. Recent MOVPE growth of V-doped GaAs [31] has confirmed this interpretation. It was shown that only less than 1% of vanadium atoms in GaAs MOVPE layers are electrically active.…”
Section: Tm-doped Si Gaas Crystalssupporting
confidence: 56%
“…It was shown that only less than 1% of vanadium atoms in GaAs MOVPE layers are electrically active. Furthermore, attempts to create a V-related complex (suggested by many authors) by implantation into GaAs of V, O, V+O, Si+V+O, and S+V+O, for variety of doses and at different energies, have led to an unequivocally negative result [31] .…”
Section: Tm-doped Si Gaas Crystalsmentioning
confidence: 99%
“…The ultra-high-purity VO(OC 2 H5) 3 source was held at 10'C in a thermostatic bath. The detailed processes of the growth and chemical analysis were described in a previous report [5]. Some of the samples were additionally doped with Si and/or Be in order to systematically vary the Fermi levels in the epitaxial layer and change the charge state of the vanadium.…”
Section: Methodsmentioning
confidence: 99%